The Influence of Working Capital and Inventory Turnover on Profitability through Operational Efficiency at PT Pixel Detail Indonesia - Hamsah Halim; Muhammad Akob Kadir; Muhammad Tafsir; Baharuddin Baharuddin (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of working capital turnover and inventory turnover on profitability and tests the mediating role of operational cost efficiency at PT Pixel Detail Indonesia during 2018–2025. Research Method: A quantitative explanatory-causal longitudinal design was employed using 32 quarterly financial statements. Working capital turnover and inventory turnover were independent variables, BOPO represented operational cost efficiency, and ROA represented profitability. Data were analyzed using multiple linear regression and the Sobel test with SPSS. Results and Discussion: Working capital turnover had a significant positive effect on profitability, whereas inventory turnover had no significant effect. Working capital turnover significantly affected operational cost efficiency at the one-tailed 5% level, while inventory turnover did not. BOPO negatively and significantly affected profitability, indicating that greater cost efficiency increases ROA. Operational cost efficiency did not mediate either relationship. The profitability and efficiency models explained 97.7% and 13.2% of the respective variances. Implications: Management should reduce BOPO below 50% and optimize working capital turnover. Future research should examine broader samples and alternative mediation methods. Originality: This study extends the Resource-Based View to a non-listed creative media company in eastern Indonesia using quarterly financial data.